The prison libraries: situation in the world and Turkey - Hasan Sacit Keseroğlu (Türk Kütüphaneciliği)
The aims of this book are to point out to the importance of prison library which is a crucial component in the rehabilitation  of incarcerated people and to reveal the problems of prison  libraries generally worldwide and particularly in Turkey, based on a comprehensive national survey. As a conclusion, an organizational and collaboration model is suggested to solve the problems and to improve the status of the prison libraries in Turkey.